Rekonstruksi Ruang Peri-Urban: Interaksi Sosial-Ekonomi Dalam Dinamika Kutub Pertumbuhan dan Proses Gentrifikasi di Kawasan Perkotaan Bulukumba - Isra, Muhammad; Sakti, Harry Hardian; Radhinal, Yan; Ahmad, Despry Nur Annisa (Prodi PWK Universitas Tadulako, 2025)
The urban development of Bulukumba Regency exhibits a spatial expansion trend toward peri-urban areas, historically marked by the emergence of new growth poles. This phenomenon reflects ongoing urbanization and generates complex social dynamics through population migration from both rural and urban regions. Migration is driven by the pursuit of economic opportunities, more affordable housing, and lifestyle shifts increasingly oriented toward urban preferences. This study aims to analyze the influence of growth poles on morphological changes and to explore the role of gentrification in shaping socio-economic interaction patterns. A quantitative approach is employed, utilizing spatial analysis, correlation testing, and grounded theory to examine the phenomenon holistically. The findings indicate that both physical and non-physical factors are influenced by fragmented growth patterns, often concentrated around economic potential and high accessibility. The formation of growth poles is seen as a consequence of leapfrogging centrifugal urban expansion, whereby central urban development stimulates the emergence of new development clusters in peri-urban zones. These zones act as transitional spaces offering economic opportunities with lower living costs, making them attractive destinations for urban migrants facing socio-economic pressures in their places of origin. Gentrification is not merely a physical revitalization process but also functions as a socio-economic filtering mechanism that reconstructs cultural identity and values within industrialized spaces. The shift from an agrarian to an urban economy marks a structural transformation shaped by market efficiency, competitiveness, and the rationality of spatial capitalism.